2019
DOI: 10.1371/journal.pone.0210514
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiotherapy for prostate cancer with seminal vesicle involvement (T3b): A multicentric retrospective analysis

Abstract: ObjectivesNo study has reported clinical results of external-beam radiotherapy specifically for T3b prostate cancer. The possibility of escalating the dose to the involved seminal vesicles (ISV) while respecting the dose constraints in the organs at risk is thus so far not clearly demonstrated. The objective of the study was to analyze the dose distribution and the clinical outcome in a large series of patients who received IMRT for T3b prostate cancer.Materials and methodsThis retrospective analysis included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 61 publications
(67 reference statements)
1
17
0
2
Order By: Relevance
“…A number of studies provide evidence for the efficacy of dose escalation in prostate cancer [2,[14][15][16][17][18][19][20][21]. Our results are in line with previous findings that suggest that elevated dose could improve the bDFS rate in almost all risk groups [2,[14][15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A number of studies provide evidence for the efficacy of dose escalation in prostate cancer [2,[14][15][16][17][18][19][20][21]. Our results are in line with previous findings that suggest that elevated dose could improve the bDFS rate in almost all risk groups [2,[14][15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…For very high risk group, Narang et al reported 46% of 10-year bDFS including 82% of 3D-CRT and 18% of IMRT with prescribed dose 70.2 Gy (64.8–75.6 Gy) [ 13 ]. Goupy et al reported a 5-years bDFS rate of 75.2% in T3bN0 disease with 74 (70–76) Gy of IMRT (FU 26 months) in French population [ 14 ]. Ishiyama reported 5-year bDFS of 81.9% using HDR + EBRT [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations